Equitable health services for the young? A decomposition of income-related inequalities in young adults' utilization of health care in Northern Sweden. Issue 1 (December 2017) - Mosquera, Paola; Waenerlund, Anna-Karin; Goicolea, Isabel; Gustafsson, Per
Abstract Background Despite the goal of the Swedish health system to offer health care according to the principle of horizontal equity, little is known about the equality in access to health care use among young people. To explore this issue, the present study aimed i) to assess horizontal inequity in health care utilization among young people in Northern Sweden; and ii) to explore the contribution of different factors to explain the observed inequalities. Methods Participants (N = 3016 youths aged 16–25 years) came from the "Health on Equal terms" survey conducted in 2014 in the four northernmost counties in Sweden. Concentration indices (C) and horizontal inequity indices (HI) were calculated to measure inequalities in the utilization of two health care services (general practitioners (GP) and youth clinics). The HI was calculated based on health care utilization and variables representing socioeconomic status (household income), health care needs factors and non-need factors affecting health care use. A decomposition analysis was carried out to explain the income-related inequalities. Results Results showed a significant positive income-related inequality for youth clinic utilization in women (C = 0.166) and total sample (C = 0.097), indicating that services were concentrated among the better-off. In contrast, general practitioner visits showed inequality pointing toward a higher utilization among less affluent individuals; significant in women (C = −0.079), men (C = −0.101) and pooled sample (C = −0.097). After taking health care needs into consideration, the utilization of youth clinics remained significantly pro-rich in women (HI = 0.121) and total sample (HI = 0.099); and consistently pro-poor for the GP visits in the pooled sample (HI = −0.058). The decomposition analyses suggest that socioeconomic inequalities explain a considerable portion of the pro-rich utilization of youth clinics services among young women. The corresponding analyses for GP visits showed that need factors and socioeconomic conditions accounted for the pro-poor concentration of GP visits. Conclusion The distribution of GP visits among young people in Northern Sweden slightly favored the low-income group, and thus seems to meet the premises of horizontal equity. In contrast, the findings suggest substantial pro-rich horizontal inequity in the utilization of youth clinics among young women, which are largely rooted in socioeconomic inequalities.